Efectos de los disturbios generados por diferentes estrategias de manejo sobre los estratos vegetales de bosques de Nothofagus antarctica de Chubut, Argentina ... : آثار الاضطرابات الناتجة عن استراتيجيات الإدارة المختلفة على الطبقات النباتية لغابات نوثوفاغوس القطبية الجنوبية في تشوبوت، الأرجنتين ... - Romina Lorena Gönc; Ricardo Casaux; Daniel Szulkin-Dolhatz (OpenAlex, 2015)
Nothofagus antarctica is a species of the Andean-Patagonian forest with a wide distribution from the north of Neuquén to Tierra del Fuego. Although the N. antarctica forests are of great economic importance for the region, they are intensely affected nowadays by human activities such as grazing, firewood extraction, conversion into pastures and the replacement by coniferous plantations. These activities produce changes in the N. antarctica forest, mainly by the alteration of its original structure affecting the performance of the ecosystem as a whole, resulting in the loss of biodiversity. Since July 2008 up to May 2010 in the northwest of Chubut, Patagonia, we analyzed the effect of disturbances associated with different management strategies on species composition and structure of N. antarctica forest. The disturbances on N. antarctica forest considered in this study are derived from extraction of firewood by patches and landscapes, conversion of forests into pastures, forest fires occurred 15 and 25 years ... : نوثوفاغوس أنتاركتيكا هو نوع من غابات الأنديز- باتاغونيا مع انتشار واسع من شمال نوكين إلى تييرا ديل فويغو. على الرغم من أن غابات أنتاركتيكا الشمالية ذات أهمية اقتصادية كبيرة للمنطقة، إلا أنها تتأثر بشدة في الوقت الحاضر بالأنشطة البشرية مثل الرعي واستخراج الحطب والتحويل إلى مراعي والاستعاضة عنها بالمزارع الصنوبرية. تنتج هذه الأنشطة تغييرات في غابة أنتاركتيكا الشمالية، ويرجع ذلك أساسًا إلى تغيير هيكلها الأصلي الذي يؤثر على أداء النظام البيئي ككل، مما يؤدي إلى فقدان التنوع البيولوجي. منذ يوليو 2008 حتى مايو 2010 في شمال غرب تشوبوت، باتاغونيا، قمنا بتحليل تأثير الاضطرابات المرتبطة باستراتيجيات الإدارة المختلفة على تكوين الأنواع وهيكل غابة أنتاركتيكا الشمالية. الاضطرابات في غابات أنتاركتيكا الشمالية التي تم النظر فيها في هذه الدراسة مستمدة من استخراج الحطب عن طريق البقع والمناظر الطبيعية، وتحويل الغابات إلى مراعي، وحرائق الغابات التي حدثت قبل 15 و 25 عامًا. كانت الغابة البكر تعتبر عنصر تحكم. يختلف الهيكل والتكوين وتنوع الأنواع بين الغابات المتأثرة باضطرابات مختلفة. لوحظ ارتفاع الغطاء الشجري وطبقات الشجيرات في ...